COMPARISON OF WPA2 EAP-PSK AUTHENTICATION SYSTEM ON WIRELESS NETWORK WITH PENETRATION TESTING METHOD USING FLUXION TOOLS - Stefanus Eko Prasetyo; Try Windranata (Universitas Internasional Batam, 2022)
Wireless Network is a collection of electronic devices that connect to each other using air devices or frequencies as a data traffic flow. Today, there are many users who use WPA2-PSK or WPA2-EAP as a wireless network security system that aims to prevent people from accessing it without permission. This research uses a wireless penetration testing technique that uses fluxion tools by comparing and analyzing the WPA2 authentication security system with EAP-PSK on a wireless network which aims to determine the vulnerability of a network security system. To carry out penetration testing, the author refers to the